Improvement of xylanase production by recombinant Escherichia coli DH5α using fed-batch fermentation - Basar, Bazilah (2011)
The past few decades of the twentieth century have witnessed spectacular advances and improvement of living standards due to the beneficial integration of novel and brilliant ideas with scientific progress and rapid translation of laboratory findings into practical technologies and commercial-scale manufacturing processes. In the field of chemical technology, the need for safer and ‘environmental friendly’ technologies has become imminent where manufacture of a variety of products on large scale has resulted in serious effluent and hazardous waste disposal problems. In recent years, there has been an increasing demand of xylanase enzyme production regarding their wide applications in various industries, especially in paper and pulp industry. The production of xylanase from wild microorganisms (bacterial, fungal and yeast) were commonly associated with other enzymes such as cellulases and mannases, where purification of xylanases increase the production cost. The xylanase producing-fungi normally have low growth rate thus correspond to lower enzyme productivity which limits its application in commercial fermentation processes. In addition, the metabolic enzymes of xylanase producer such as proteases and transglycosides also affect the actual yield of xylanase. Alternatively, enhanced enzyme production by ecombinant strain such as Escherichia coli may be used to overcome these problems. Recombinant enzyme production by E. coli generates higher productivity and yield due to faster growth rate compared to fungal producers. The bacterium, E. coli DH5α harbouring phagemid pTP510 was used throughout this study for the production of xylanase. The genes encoding exo-xylanase (exo-xyn), - Larabinofuranosidase (abfa), and β-xylosidase (xyl) were isolated from a thermophilic bacterium Geobacillus thermoleovorans IT-08. Preliminary, the nutrients requirement by the recombinant E. coli DH5α for improvement of intracellular xylanase production was investigated in shake flask culture. The effect of the different levels of dissolved oxygen tension on growth of E. coli DH5α and xylanase production was carried out in 2 L stirred tank fermenter using optimal medium. The bulk of batch fermentation data were analyzed to generate kinetic parameter values and to develop kinetic models of the fermentation process. Fed-batch fermentation modes were developed using kinetic parameter values and information generated from the preliminary batch fermentation data. Constant and exponential fed-batch fermentations were carried out using 2 L stirred tank fermenter equipped with Multi Fermenter Control System (MFCS) to control the feeding rate of feeding medium into the culture according to the proposed algorithm. Among the two basal media tested, defined mineral medium gave higher growth and xylanase production as compared to complex medium of Luria Bertani. The optimal glucose and (NH4)2SO4 concentration added to the basal medium for xylanase production was obtained at 10 g L-1 and 2 g L-1, respectively. Growth of E. coli DH5α and xylanase production was inhibited in oxygen limited fermentation, where dissolved oxygen tension level was controlled at 0% saturation. On the other hand, xylanase production was enhanced at DOT level controlled at 20% saturation, though growth was not significantly improved. The production of xylanase in batch fermentation using optimal medium composition and DOT level was 1784.57 U mL-1. This gave the overall xylanase productivity and yield of 91.43 U mL.h-1 and 0.1190 U xylanase g glucose-1, respectively. The proposed models based on logistic and Luedeking-Piret equations were found sufficient to describe growth of E. coli DH5α in different medium formulation and DOT levels. Among the different feeding rates (0.025, 0.050 and 0.075 L h-1) employed in constant fed-batch fermentation, the highest cell concentration (10.82 g L-1) xylanase activity (1920.56 U mL-1) was obtained at a feeding rate of 0.050 L h-1. In this fermentation, low concentration of residual glucose (0.028 g L-1) was observed, which was associated with very small quantity of acetic acid accumulated in the culture. In exponential fed batch fermentation, the highest cell concentration (10.33 g L-1) and xylanase activity (1939.99 U mL-1) was obtained at specific growth rate (μ ) of 0.15 h-1. Very low residual glucose (0.004 g L-1) and very small quantity of acetic acid was detected throughout this fermentation run. The final cell concentration obtained in fed-batch fermentation (10.33 g L-1) was about 6.5% higher than that obtained in optimal batch fermentation (6.26 g L-1). On the other hand, the production of xylanase (1939.99 U mL-1) in optimal exponential fed-batch fermentation was about 8.7% higher than that obtained in optimal batch fermentation (1784.57 U mL-1) in 2 L stirred tank fermenter. However, the overall xylanase productivity obtained in exponential fed-batch fermentation (58.71 U mL-1 h-1) was very much reduced as compared to that obtained in batch fermentation (91.43 U mL.h-1).This is very much dependent on the ability of E. coli DH5α to express xylanase enzyme based on medium composition and growth morphology. These results indicate that efficient process control strategy is important for the improvement of xylanase production by E. coli DH5α